Tuesday

January 27, 2015

January 27, 2015

Posted by **jenny** on Wednesday, February 6, 2013 at 3:46pm.

- maths -
**Steve**, Wednesday, February 6, 2013 at 3:52pma*b = a*c

a*b - a*c = 0

a*(b-c) = 0

if a≠0, b-c = 0, since the product is zero.

b-c = 0

b = c

a^b = a^c

a^b / a^c = 1

a^(b-c) = a^0

b-c = 0

b = c

**Answer this Question**

**Related Questions**

physics - A condition for mechanical equilibrium is that the sum of the forces ...

Maths Help - (1) Prove that the cancellation law of multiplication is equivalent...

Physics - partscoretotalsubmissions1--10/12--10/13--10/14--10/1----4--The tail ...

maths - Prove : (a^2+b^2+c^2+d^2)(1/a^2+1/b^2+1/c^2+1/d^2)greater equal to 16

maths - Prove : (a^2+b^2+c^2+d^2)(1/a^2+1/b^2+1/c^2+1/d^2)greater equal to 16

maths - My question is prove that e^logx is equal to x

maths - n! is greater or equal to 2^n-1 prove by induction

maths - prove that if m is not equal to n, the equation (m^2+n^2)x^2 - 2(m+n)x...

discrete math - 1)prove that if x is rational and x not equal to 0, then 1/x is ...

Discrete Math - Prove that if a and b are integers with a not equal to zero and ...